Bulgaria - Administrative and regulatory barriers to business - World Bank (World Bank, 2012)
The present report on the Administrative and Regulatory Barriers to Business is part of an ongoing World Bank analytical and advisory support to the Government of Bulgaria in the area of regulatory reform. Since 2006, the World Bank has provided analytical and advisory support to the government in this area. In 2007, the Bank reviewed administrative procedures in the tourism, food, and road transportation sectors, calling for reduction and simplification of certain burdensome administrative regimes and emphasizing superfluous regulation at the municipality level. This report aims to identify ways in which Bulgaria can further remove obstacles to business regulation, recognizing that achieving pre-crisis growth levels, raising labor productivity and improving the business environment will require continued reforms to eliminate administrative and regulatory barriers to business. The report serves three purposes, such as: 1) providing the economic backdrop and comparators of Bulgaria's regulatory environment; 2) reporting on survey results including assessments by and perceptions of senior managers of Bulgarian enterprises; and 3) identifying strategic reform recommendations, including regulatory changes, institutional upgrading and capacity building, and legislative amendments.